A non-field analytical solution of the Luikov equations for simultaneous heat and mass transfer - Vladimir Kulish; Bui Thanh Phan; Vladimír Horák (Results in Engineering)
Non-field solutions to the Luikov equations for simultaneous heat and mass transfer have been derived using the method of Kulish. These solutions provide simple-to-use formulae for estimating transient values of temperature and mass (moisture) content as functions of heat and mass fluxes. The approach simplifies the modelling process by bypassing complex boundary conditions and eigenvalue calculations. Validation was performed using two limiting cases of geometry – planar and spherical – under constant heat flux conditions. The results demonstrated good agreement with experimental data, underscoring the accuracy and practical applicability of the derived solutions for engineering purposes such as drying processes.